Kenneth MacMillan and the Subject Matter of Ballet. Issue 2 (4th May 2019) - De Lucas, Cristina
Abstract: Sex, violence, and visceral elements of similar dramatic tenor feature frequently in ballets by the British choreographer Kenneth MacMillan. Although he publicly acknowledged the decisive impact of John Osborne's play Look Back in Anger on his artistic vision, little detail is known about how his inclination toward unconventional topics was formed. By revisiting primary and secondary sources about MacMillan's life and career, and by considering them within the context of postwar British dance and drama, this article explores how this tendency toward dramatic subject matter progressively took shape during his first years as a choreographer and purposely crystalized in 1960 with his ballet The Invitation.